Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

La santé des populations de langue officielle en situation minoritaire [numéro thématique] - Leis, Anne; Bouchard, Louise (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)
Cette page éditoriale présente un numéro spécial de la Revue canadienne de santé publique qui comporte 16 articles compilant certains résultats de recherches obtenus par des chercheurs affiliés au RISF, au RRASFO et à l’Institut de recherche de l’Hôpital Montfort (IRHM), ainsi qu'un commentaire exposant les enjeux d'accès aux services de santé linguistiquement concordant au Pays de Galles.
fs-ref-orig: Leis, A. et Bouchard,

Minorités de langue officielle du Canada : égales devant la santé ? - Bouchard, Louise; Desmeules, Martin (Presses de l’Université du Québec, 2011)

Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

La santé en francophonie canadienne : vivre en situation minoritaire influence-t-il la santé ? - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène (Bulletin de l’association des médecins de langue française, 2009)
La littérature suggère l'hypothèse d'une santé différentielle des francophones en situation minoritaire au Canada. L'effet de minorité sur la santé perçue a été mesuré à l'aide des Enquêtes sur la santé dans les collectivités canadiennes (ESCC) de 2001 et 2003. Une analyse de régression logistique multivariée séquentielle montre que les francophones minoritaires – hommes et femmes – sont plus enclins à déclarer une moins bonne santé que les anglophones majoritaires. Contrairement aux femmes, cette disparité chez les hommes demeure significative même lorsque nous ajustons pour certains grands déterminants de la santé. L'étude illustre que l'action des déterminants de santé peut être ainsi modulée par le rapport minoritaire/majoritaire. Les inégalités ainsi révélées appellent à une réflexion sur les politiques d'accès linguistique aux soins de santé.

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H. et Mukaneza, A. (2018). Profil santé des communautés anglophones en situation minoritaire au Québec [infographie]. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2018e

Health profile of English-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H., & Mukaneza, A. (2018). Health profile of English-speaking minority communities in Quebec [infographic]. University of Ottawa and Institut du savoir Montfort. fs-code-orig: Bouchard-2018f

Profil santé des communautés anglophones minoritaires au Québec [infographie] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H. et Gagnon-Arpin, I. (2009). Profil santé des communautés anglophones minoritaires au Québec [infographie]. Réseau de recherche interdisciplinaire sur la santé des francophones en contexte minoritaire au Canada (RISF). Santé Canada. fs-code-orig: Bouchard-2009e

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gagnon-Arpin, Isabelle (2009)

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

La santé en situation linguistique minoritaire - Bouchard, Louise; Gaboury, Isabelle; Chomienne, Marie-Hélène; Gilbert, A.; Dubois, L. (Politiques de Santé, 2009)
fs-ref-orig: Bouchard, L., Gaboury, I., Chomienne, M.-H., Gilbert, A. et Dubois, L. (2009). La santé en situation linguistique minoritaire. Politiques de Santé, 4(4), 36-42. https://www.ncbi.nlm.nih.gov/pmc/Article de revue s/PMC2700700/pdf/policy-04-036.pdf fs-code-orig: Bouchard-2009a

Physical inactivity among Francophones and Anglophones in Canada - Imbeault, Pascal; Makvandi, Ewa; Batal, Malek; Gagnon-Arpin, Isabelle; Grenier, Jean; Chomienne, Marie-Hélène; Bouchard, Louise (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objective Leisure-time physical activity participation is influenced by various socio-demographic factors. Recent evidence suggests that being part of a minority negatively impacts an individual’s health status. The objective of this study was to compare inactive leisure-time physical activity between the Francophone minority and the Anglophone majority in Canada. Methods Data from the fusion of cycles 2.1, 3.1, 4.1, 2008 and 2009 of the Canadian Community Health Survey (CCHS) were used. The linguistic variable was determined by languages spoken at home, first language learned and still understood, language of interview, and language of preference. Leisure-time physical activity was based on a questionnaire provided during the interview. Factors associated with inactive leisure time were examined using logistic regression models. Results Francophones were more likely than Anglophones to be physically inactive in their leisure time (49.1% vs. 47.2%). A greater percentage of Francophones had poor self-perceived health, were older, were single, had lower education, had higher rate of unemployment and lived in rural areas compared to Anglophones. When these socio-demographic factors were taken into account, there were no further differences in the likelihood of being inactive between Francophones and Anglophones. Conclusion The Francophone minority in Canada is characterized by socio-demographic factors that have a negative impact on leisure-time physical activity participation.